Controle social do espaço público: uma análise do conselho turístico pólo costa das dunas - Gonçalves, Joyce de Souza (2007)
The managing Conselho of public politics constitute one of the main experiences of democracy in Brazil contemporary representing a conquest for construction of a democratic institutionalism. The historical newness consists of the intensification and the institutionalization of the dialogue between government and society - in public and plural canals - as condition for an allocation more efficient joust and of the public resources. In this context the present study it objectified to understand from readings of the performance of represented group of bencheses the dynamics of functioning of the Tourist Conselho Pólo Costa das Dunas while space of participation and social control. The bibliographical research contemplated diverse sources in order to compile knowledge of credential authors in the quarrel of inherent subjects to the civil society and the public sphere to the construction of the citizenship to the conception formation and dynamics of the social control through Conselho of public politics. A qualitative perspective the case study was adopted as research method and for attainment of the data interviews with the members of the Conselho had been carried through beyond consultation the referring documents the dynamics of functioning of the Conselho. The profiles capacities and limitations of the members of the Conselho had been identified constitution social and dynamic organization of functioning of the Conselho and the readings of the members of the Conselho concerning the power to decide instances and participation. The results had shown that the allotment of being able in the Conselho does not occur of equal form. The functions of coordination of the activities of the Conselho are assumed by the representatives of the public agencies. Level of qualification of council members also if presents as difficulty to development of activities of Conselho since the majority of the interviewed ones disclosed unreliability and unfamiliarity when thematic specific that runs away from its organizacional reality they are boarded in the assemblies. Of this form the Conselho if presents more as half of institutional legitimation of what half of characterization of the creation of a public sphere properly said. Finally he could himself be concluded that a democratic culture inexists that inside crosses practical the institutional ones of the Conselho thus limiting the possibility to reach the effective social control of the public politics of tourism in the Rio Grande do Norte